Immigration policy and belonging: ramifications for DACA recipients’ sense of belonging - Mallet-Garcia, ML; García-Bedolla, L (SAGE Publications, 2021)
The socioeconomic benefits of the Deferred Action for Childhood Arrivals program initiated in 2012 by executive order from then-president Obama have been documented in the recent literature. However, the consequences of the legal challenge brought against the program by the Trump administration have not yet been fully examined. This article analyzes qualitative data from Latino Deferred Action for Childhood Arrivals recipients in California to assess how the legal turmoil around the program is affecting their sense of belonging in the United States. We find that the uncertainty around the program has negative consequences on their sense of belonging, despite the program’s aims at improving it, and despite the respondents’ living in a rather welcoming state in terms of state-level immigration policies. Notably, we find that respondents feel increasingly alienated from and unwanted in American society and postpone major life goals.